2009
DOI: 10.1093/eurheartj/ehp487
|View full text |Cite
|
Sign up to set email alerts
|

Normal weight obesity: a risk factor for cardiometabolic dysregulation and cardiovascular mortality

Abstract: Normal weight obesity, defined as the combination of normal BMI and high BF content, is associated with a high prevalence of cardiometabolic dysregulation, metabolic syndrome, and CV risk factors. In women, NWO is independently associated with increased risk for CV mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
409
5
38

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 540 publications
(495 citation statements)
references
References 42 publications
19
409
5
38
Order By: Relevance
“…Recent studies have shown that the amount of adipose tissue in subjects with normal BMI provides incremental prognostic value, particularly in women. 10 The results of this meta-analysis suggest that the current definition of obesity at the individual level needs to be reassessed. Although obesity means excess body fat, the current definition of obesity is based on body weight regardless of its composition.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Recent studies have shown that the amount of adipose tissue in subjects with normal BMI provides incremental prognostic value, particularly in women. 10 The results of this meta-analysis suggest that the current definition of obesity at the individual level needs to be reassessed. Although obesity means excess body fat, the current definition of obesity is based on body weight regardless of its composition.…”
Section: Discussionmentioning
confidence: 95%
“…8,9 Furthermore, excess body fat percent (BF%) has been shown to be associated with metabolic dysregulation regardless of body weight. 10 Thus, it is imperative to know the accuracy of BMI to identify body adiposity to justify its use in clinical practice to either diagnose or rule-out excessive body adiposity at the individual patient level.…”
Section: Introductionmentioning
confidence: 99%
“…29,53,54 The few studies analyzing the influence of BF% on cardiometabolic risk factor levels have been predominantly aimed to compare the influence of body fat distribution than to analyze the effect of increased adiposity itself 32,47,55,56 or have been performed in volunteers with BMI values within Relevance of body fat for metabolic risk J Gómez-Ambrosi et al the lean range. 20 In this sense, BF% shows lower, 56 similar, 47 or higher 57 correlation with metabolic risk factors than central adiposity measures, but has been recently suggested as a better indicator of coronary heart disease risk than waist circumference. 32 The present study emphasizes that anthropometric indicators of body fat distribution such as waist circumference or waist-to-hip ratio are important when evaluating the risk of a subject regardless of its body weight.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7] These cutoffs are very useful in epidemiological studies 8 but in spite of its wide use BMI is only a surrogate measure of body fatness and does not provide an accurate measure of body composition. [8][9][10][11][12][13][14][15][16][17][18][19][20][21] Noteworthy, obesity is defined as an excess accumulation of body fat, with the amount of this excess fat actually being responsible for most obesity-associated health risks. 22 Obesity increases the risk of cardiovascular diseases and type 2 diabetes 23,24 at the same time as imposing functional limitations in a number of subjects, which translate into a reduced quality of life as well as life expectancy.…”
Section: Introductionmentioning
confidence: 99%
“…Some individuals at healthy weights have what has been referred to as "normal-weight obesity," a condition characterized by high body fat and lower lean muscle mass while still falling within the BMI parameters of "healthy" weight. 8 This study is innovative in examining abnormal blood glucose in healthy weight adults, a population previously believed to be at low risk of glucose abnormalities. Because typical strategies to prevent prediabetes or Type 2 diabetes (e.g., calorie restriction and weight reduction) are inappropriate for individuals who are not overweight, it is unclear whether physical activity moderates the presence of abnormal glucose in this healthy weight population.…”
Section: Iabetes Has Reached Epidemic Proportionsmentioning
confidence: 99%